BINTU SYATI’ DAN PENAFSIRANNYA TERHADAP SURAH AL-‘ASR DALAM KITAB AT-TAFSIR AL-BAYANI LIL QUR’ANIL KARIM - Ramadhani, Wali (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2018)
This article discusses about the biography of Bintu Syati? and her bayani interpretation. Her Interpretation work titled at-Tafsir al-Bayani lil Quranil Karim is the best representation of the methodology of the Quran interpretation with a literary nuance initiated by her own husband, Amin al-Khuli. The author, in this article, also describes the application of Bayani interpretation method in QS al-?Asr.